Pengaruh Penggunaan Media Power Point (PPT) Interaktif terhadap Hasil Belajar Siswa SMP Negeri 3 Kabila - Danial Y. Husuna; Syarwani Canon; Ardiansyah, Ardiansyah; Meyko Panigoro; Rierind Koniyo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to analyze the effect of using interactive PowerPoint media on the learning outcomes of eighth-grade students at SMP Negeri 3 Kabila. The study was motivated by the relatively low student learning outcomes in Social Studies, as indicated by the number of students who had not yet achieved the minimum mastery criteria, as well as the limited use of technology-based instructional media in classroom learning. This research employed a quantitative approach with a correlational design. The population and sample consisted of 50 eighth-grade students. Data were collected through questionnaires, observation, interviews, and documentation. The data were analyzed using simple linear regression after the instruments had met validity and reliability requirements and the data were normally distributed. The findings revealed that the use of interactive PowerPoint media had a positive and significant effect on student learning outcomes. This was indicated by a t-value of 6.184, which was higher than the t-table value of 2.008 at a 5 percent significance level. The correlation coefficient of 0.666 indicated a strong relationship, while the coefficient of determination of 0.443 showed that 44.3 percent of the variance in students’ learning outcomes was explained by the use of interactive PowerPoint media. Therefore, interactive PowerPoint media can be considered an effective instructional alternative to support the improvement of student learning outcomes.